Analisis Swot Pelaksanaan Program One Village One Product (OVOP) pada Koperasi Mitra Tani Parahyangan Cianjur - Zainal Arifin H Masri (Sosio e-Kons, 2018)
ABSTRACT This research was conducted at Cooperative Mitra Tani Parahyangan, Tegalega Village, Warungkondang Sub-district, Cianjur District. The study was carried out in the area with the following considerations: First, the existence of possible problems to be investigated; Second, is the best producer and breeder of Horticulture Agribusiness in West Java; Third, one of the pilot projects of the successful implementation of OVOP in West Java, many received national awards and has a strong market network with partners outlets spread across JABODETABEK. This study aims to: (1) describe the implementation of the One Village One Product (OVOP) program implemented in Cooperative Mitra Tani Parahyangan Cianjur, (2) to describe the factors of Strengths, Weakness, Opportunities and Threats (threat), which is in Cooperative Mitra Tani Parahyangan Cianjur (3) to analyze development strategy applied by Cooperative Mitra Tani Parahyangan Cianjur in running One Village One Product (OVOP) program. For the first and second objectives of this study, we used a case study method with qualitative descriptive analysis to describe the implementation of One Village One Product (OVOP) program implemented in Cooperative Mitra Tani Parahyangan Cianjur, and the existing Strengths, Weakness, Opportunities, and Threats factors. For the third purpose of analyzing development strategy applied by Cooperative Mitra Tani Parahyangan  in supporting One Village One Product (OVOP) program used SWOT analysis Keywords: OVOP, case study, qualitative descriptive, SWOT analysis,